2007
DOI: 10.1073/pnas.0706547105
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of AHK1/ATHK1 and cytokinin receptor histidine kinases in response to abscisic acid, drought, and salt stress in Arabidopsis

Abstract: In plants, multistep component systems play important roles in signal transduction in response to environmental stimuli and plant growth regulators. Arabidopsis contains six nonethylene receptor histidine kinases, and, among them, AHK1/ATHK1, AHK2, AHK3, and CRE1 were shown to be stress-responsive, suggesting their roles in the regulation of plant response to abiotic stress. Gain-and loss-of-function studies in Arabidopsis indicated that AHK1 is a positive regulator of drought and salt stress responses and abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

33
559
4
9

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 585 publications
(605 citation statements)
references
References 30 publications
33
559
4
9
Order By: Relevance
“…The CK receptors AHK2 and AHK3 were previously reported to act as negative regulators in drought response (10,12). However, the physiological and molecular mechanisms by which the CK signaling acts, the stress-related specific functions of other TCS components, and the identification of downstream components of CK phosphorelay involved in the regulation of drought response were not completely understood and required further in-depth characterization (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CK receptors AHK2 and AHK3 were previously reported to act as negative regulators in drought response (10,12). However, the physiological and molecular mechanisms by which the CK signaling acts, the stress-related specific functions of other TCS components, and the identification of downstream components of CK phosphorelay involved in the regulation of drought response were not completely understood and required further in-depth characterization (7).…”
Section: Discussionmentioning
confidence: 99%
“…We previously published that the ahk2,3 double mutant, which has a distinguishable shoot growth retardation phenotype in comparison with other single and double combinations of ahk2, ahk3, and ahk4 genes, possessed the strongest drought-tolerant phenotype (10). To further characterize the functional role of the five Arabidopsis AHPencoding genes in drought stress response, we collected various combinations of ahp mutants from available public resources (13).…”
Section: Ahp235mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, AHK1, another homolog of the cytokinin receptors, has been shown to be involved in both the stress response and seed maturation (Urao et al, 1999;Tran et al, 2007;Wohlbach et al, 2008). Interestingly, several type-A ARR genes are coexpressed with AHK1, and different combinations of multiple arr mutants show altered responses to osmotic stress (Wohlbach et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have shown that ATHK1 mRNA is highly expressed in root tissue, compared with other tissues, and rapidly accumulates in response to changes in soil salinity or osmotic variation, thus making it a highly efficient sensor to environmental fluctuations [8,12,13]. Recent research revealed that ATHK1 plays a unique role in the regulation of processes controlling desiccation, which occur during seed formation.…”
mentioning
confidence: 99%